Development of the "Day 100 Talk": Addressing existing communication gaps during the early cancer treatment period in childhood cancer. Issue 6 (31st January 2018) - Feraco, Angela M.; Brand, Sarah R.; Gagne, Joshua; Sullivan, Amy; Block, Susan D.; Wolfe, Joanne
Abstract: Background: Families' communication needs during the early cancer treatment period (ECTP) may not be optimally met by current practices. We sought to identify potential communication gaps and to ameliorate these by developing a novel in‐depth conversation between families and their pediatric oncologists, the "Day 100 Talk" (D100), during the ECTP. Procedure: We conducted semistructured interviews with parents and patients undergoing childhood cancer treatment for < 7 months. Interviews sought to elicit perceived communication gaps regarding cancer care and inform D100 development. Following qualitative analysis of interview responses, we developed a three‐part D100 conversation tool consisting of a preparatory family worksheet, a conversation guide, and a family summary sheet. We presented the tool during interviews and a focus group with pediatric oncology providers and revised it to incorporate provider input. Results: Twenty‐two stakeholders (six parents, five adolescents, and 11 providers) participated in interviews or a focus group. Parents and patients perceived insufficient anticipatory guidance as the most important communication gap. They also reported sometimes withholding worries and cancer‐related beliefs. Meanwhile, oncology providers worried about "opening Pandora's Box" and limited clinical time. Additionally, providers reported employing indirect methods such as surmising to determine families' needs and relying on psychosocial clinicians to engage families around potentially "taboo" issues of emotional coping and spirituality. Conclusion: Creating a communication occasion (D100), ensuring complementary disciplinary expertise through joint participation by oncologists and psychosocial clinicians, and providing a conversation tool to prompt disclosure by families and facilitate anticipatory guidance may ameliorate existing communication gaps during the ECTP.